Synthesis of ligands for 2D organometallic networks - Liew, Mabelyn Zi Xuan (Nanyang Technological University, 2024)
The focus of this project is the synthesis and characterization of an symmetric imine containing ligand for a 2D organometallic network with transition metals, which can be used as a catalyst. Over the course of this project, methodologies like condensation reaction and nucleophilic aromatic substitution were used to achieve the synthesis of ligands that will be used in the formation of said network. This report outlines attempts made to synthesise 2,3,8,9,14,15-hexabromo-5,6,11,12,17, 18-hexaazatrinaphthylene (ML1) and 2,3,8,9,14,15-hexakisthiobenzyl-5,6,11,12,17,18-hexaazatrinaphthylene (ML2). Recommendations at the end of this report include the bubbling the reagents for a longer period for ML1 and the use of a more reactive Chlorine (Cl) compound instead of Bromide (Br) to achieve the synthesis of ML2.